2007
DOI: 10.2527/jas.2006-709
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of carbohydrases or phytase individually or in combination to diets for weanling and growing-finishing pigs1

Abstract: The overall objective of the studies reported here was to evaluate the growth and nutrient utilization responses of pigs to dietary supplementation of phytate- or nonstarch polysaccharide-degrading enzymes. In Exp. 1, growth performance and nutrient digestibility responses of forty-eight 10-kg pigs to dietary supplementation of phytase or a cocktail of xylanase, amylase, and protease (XAP) alone or in combination were evaluated. The growth response of one hundred fifty 23-kg pigs to dietary supplementation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
4
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 37 publications
9
43
4
4
Order By: Relevance
“…In addition, supplementation with the enzyme mix increased BW and ADG compared with the NC diet, resulting in similar final BW and ADG compared with the PC. These results are in agreement with several previous studies (Graham et al 1988;Zyla et al 1996;Omogbenigun et al 2004;Olukosi et al 2007). Young pigs typically have a higher ADG response to β-glucanase supplementation than finishing pigs.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In addition, supplementation with the enzyme mix increased BW and ADG compared with the NC diet, resulting in similar final BW and ADG compared with the PC. These results are in agreement with several previous studies (Graham et al 1988;Zyla et al 1996;Omogbenigun et al 2004;Olukosi et al 2007). Young pigs typically have a higher ADG response to β-glucanase supplementation than finishing pigs.…”
Section: Discussionsupporting
confidence: 83%
“…As reported by Willamil et al (2012), xylanase and glucanase were able to increase nutrient digestibility in a wheatbarley-rye-based diet, but failed to improve pig performance in a corn-based diet. Olukosi et al (2007) also suggested that xylanase would be more active in diets Note: Values are means of eight replicates with two pigs per replicate; means with lowercased letters are different at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supplemental microbial phytase in meal diets for swine, poultry and fish effectively improves phytate phosphorus utilization by these animals, decreasing phosphorus excre-tion pollution (Augspurger et al, 2003;Rutherfurd et al, 2002;Olukosi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%